Answer:
-1
Step-by-step explanation:
First, we need to work out the left-hand side.
- find g(2) → g(2) = 2 - 1 which is 1
- next, find f(1) → f(1) = 1³ which is 1
Now, we can work out the right hand side.
- find f(-1) → f(-1) = -1³ which is -1
- then, find g(-1) → g(-1) = -1 - 1 = -2
Finally we can work out the full sum: 1 + -2 = -1.
Hope this helps!
Answer:
x+y=-5.75
Step-by-step explanation:
Ⓗⓘ ⓣⓗⓔⓡⓔ
Well, you would simply need to use the distributive property!
-(2)x-(2)2+(2)y-(2)9=1
-2x-4+2y-18=1
Then you need to add/subtract so the similar numbers are together.
-2x+2y-22=1
-2x+2y=23
x+2y=-11.5
x+y=-5.75
(っ◔◡◔)っ ♥ Hope this helped! Have a great day! :) ♥
Please, please give brainliest, it would be greatly appreciated, I only a few more before I advance, thanks!
Let t represent Todd's age now.
.. 4(t -3) -(t -3) = 81 . . . . . . 3 years ago, their differnce in ages was 81.
.. 3t -9 = 81
.. t = (81 +9)/3 = 30
Todd is 30 now.
_____
You can also work this by considering "ratio units." 3 years ago, the ratio of their ages was 4:1, a difference of 3. That difference corresponds to 81 years, so each "ratio unit" represents 81/3 = 27 years. Todd's age then was 1 ratio unit, 27 years. Now, Todd's age is 30.